EFFECT OF INTELLECTUAL CAPITAL DISCLOSURE ON SHARE PRICE - Kurnia Dani Yudhitya; Diah Agustina Prihastiwi (Transpublika Publisher, 2023)
Changes and developments in technology and knowledge have an impact on the business world, making intangible assets critical to a company’s success. However, awareness about the importance of disclosure of intangible assets, especially intellectual capital, is still low. This study aims to analyze the disclosure of intellectual capital as measured using Value Added Intellectual Capital (VAIC) related to its relevance to stock prices as measured using the closing price. The population taken is companies that are listed on the Indonesia Stock Exchange, especially those in the infrastructure sector companies in 2020-2021. By using purposive sampling in the use of samples, it was found that there were 68 observations were acquired during the course of two-year observation period. The findings show that intellectual capital does not significantly affect the stock price variable. In other words, that more information about intellectual capital does not increase stock prices, and vice versa.